The Relationship Between Musculoskeletal Pain and Picky Eating: The Role of Negative Self-Labeling - Ikemoto, Tatsunori (Pain Ther, 2019)
INTRODUCTION: Picky eating appears to be associated with poor health outcomes and thus it might have a role in musculoskeletal pain in adults. However, this relationship has not been investigated yet. The aim of the present study was to determine whether the number of musculoskeletal pain regions was associated with picky eating, which was characterized by food intake balance of familiar products or self-identification. METHODS: A total of 4660 adult subjects were enrolled in this study. Picky eating was assessed in two ways; a countable score and self-identification of picky eating. For the countable score, the number of food items, which the subjects usually did not consume among a list of 11 familiar products was measured. Self-identification as a picky eater was defined through a single question. The presence of musculoskeletal pain; in the neck, low back, knee, back, or arm, within 2 months of the survey was also identified. RESULTS: Of all subjects, 2654 (56%) had musculoskeletal pain in at least one region. The prevalence of musculoskeletal pain in every region was seen as consistently higher in subjects who self-identified as picky eaters than those who were non-picky eaters. In multiple linear regression analysis, the number of pain regions was significantly associated with older age, females, self-identification as a picky eater, and low body weight, not but the countable score. CONCLUSIONS: There may be an association between musculoskeletal pain and negative beliefs about one’s own eating behaviors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40122-019-0116-2) contains supplementary material, which is available to authorized users.